Manifestation of Patriarchal Culture towards Women Legislative Candidates: An Analysis of Negative Comments on Instagram @Bebizie as a PAN Cadre in the 2024 Election - Naila Ahmad; Salwa Alfira; Clarissa Fortuna Paripurna; Firman (PT ARRUS Intelektual Indonesia, 2024)
Women's participation in politics in Indonesia is still hampered by a strong patriarchal culture, despite policies that support women's representation. This research aims to analyze the negative comments received by Bebizie Fatlanay, a female legislative candidate from the National Mandate Party (PAN), on Instagram ahead of the 2024 elections. The method used is qualitative with an analytical descriptive approach and literature study. The results showed that negative comments more often attacked personal aspects and undermined women's political abilities, thus reflecting gender stereotypes that are still rooted in society. The conclusion of this study is that patriarchal culture not only affects people's perceptions, but also limits women's participation in politics. The importance of gender education and quota policies is expected to increase support for women legislative candidates and create a more inclusive political environment.